Videoblogging in Secondary Education Language and Literature Classroom. A Practical Design - Blanch Marcos de León, Montserrat; Betancort Santos, Sonia; Martínez Avidad, Mayra (REICE. Ibero-American Journal on Quality, Effectiveness and Change in Education, 2016)
This paper offers strategies to enhance media, informational and digital literacy through the use of videoblog in Language and Literature classroom. The aim is to meet a current educative demand: finding formulas to encourage a comprehensive communicational competence for new multimedia environments, at the same time that promotes a critic attitude for traditional and digital information consumption. The tentative results of the educational practice that has been developed among the students of 3rd of E.S.O. show that students acquired skills related to the communicative and digital competence in the 21st century.